2021
DOI: 10.3389/fmed.2021.647834
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Tissue-Informed Biomaterials to Advance Pulmonary Regenerative Medicine

Abstract: Biomaterials intentionally designed to support the expansion, differentiation, and three-dimensional (3D) culture of induced-pluripotent stem cells (iPSCs) may pave the way to cell-based therapies for chronic respiratory diseases. These conditions are endured by millions of people worldwide and represent a significant cause of morbidity and mortality. Currently, there are no effective treatments for the majority of advanced lung diseases and lung transplantation remains the only hope for many chronically ill p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…As long as the interaction between cells and scaffold systems with biomolecules can be understood and controlled and on the understanding that an optimal 3D environment for tissue regeneration can be realized, 3D Nano printing will become an important tool in tissue engineering in the near future. My opinions harmonized with Campbell, et al, that crucial standpoint commanders suppose that the new COVID-19 may drive to prolonged lung harm, furthermore triggering the requirement for regenerative therapies [8]. Modern strategies for regenerative cell-based treatments use the segregation ability of human MSCs for searching lung disease pathogenesis and therapy [9,10].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…As long as the interaction between cells and scaffold systems with biomolecules can be understood and controlled and on the understanding that an optimal 3D environment for tissue regeneration can be realized, 3D Nano printing will become an important tool in tissue engineering in the near future. My opinions harmonized with Campbell, et al, that crucial standpoint commanders suppose that the new COVID-19 may drive to prolonged lung harm, furthermore triggering the requirement for regenerative therapies [8]. Modern strategies for regenerative cell-based treatments use the segregation ability of human MSCs for searching lung disease pathogenesis and therapy [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, biomaterials are a cell culture stage that can be exactly layout to guide stem cell discrimination [11,12]. Also, Campbell and colleagues reported that the COVID-19 pandemic has supplied clinical facts displaying fibrosis of lung in these patients that remain alive after the contagion [8]. It is speculated that this fibrotic reaction will not retract, leading to a concealed flourishing of chronic pulmonary disease later on.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Expanded tissue induction with regenerative medicine extended the boundaries of the repair concept in clinical practice. [6,7] The introduction of technologies represented by 3D printing technology created conditions for solving difficult problems such as complex/composite materials, the synergy of multiple tissues and organs, and personalized repair of specific parts. [8,9] The application of bioactive ceramics in bone tissue repair is increasing, and the introduction of new technologies/methods has generated various innovative devices.…”
Section: Introductionmentioning
confidence: 99%